Konsep Pemikiran Doni Koesoema Albertus Tentang Pendidikan Karakter Ditinjau Dari Pandangan Pendidikan Islam - Purnamansyah (Sekolah Tinggi Agama Islam (STAI) Al-Amin Dompu, 2023)
Character education according to Doni Koesoema Albertus' view is that which comes from rational or personal reasoning with various dimensions, both from within and from outside one's self. In the view of Islamic education, the basis of character education is the Al-Quran and As-Sunnah. Character according to Doni Koesoema Albertus is the reality of the child's ability in his own observations. Meanwhile, in the view of Islamic education, the factors that influence character are behavior or habits. According to Doni Koesoema Albertus is to motivate educational performance and as a demand in society. Meanwhile, according to the view of Islamic education, the purpose of character education is character education in the family, local, national and international environment through customs, laws and orders between nations; develop consistent character or character in making decisions in social life; to deal with problems in society rationally; use good experiences for the formation of awareness and responsibility for their actions. The teacher referred to in Doni Koesoema Albertus's thinking is a teacher as a character educator in society who is characterized by changing values ​​to increase vision and inspiration for the performance of educational institutions. Whereas in the view of Islamic education, the teacher is a reciprocal relationship that aims to change the behavior of students towards moral maturity that is capable and provides a number of knowledge and guides them. according to Doni Koesoema Albertus is to find out the extent of the character possessed by students. Meanwhile, in the view of Islamic education, the evaluation of character education is intended to determine success in teaching, with indicators of the character that students can have.